Renascença extraordinária : dinâmica social e produtiva em transformação no Cariri Paraibano - Moraes, Carla Gisele Macedo Santos Martins (2018)
This research analyzes new social and productive dynamics at production of renaissance lace in Cariri of Paraíba, Brazil, engendered by tension and dialogue between, on the one hand, the intervention of public and private agents in the activity and, on the other hand, the perception, incorporation and re-elaboration of recent devices by the artisans, in a dialogical interaction in transformation. The intention is to unveil how a local handicraft, traditionally produced in domestic environment, socially constructed from community relations and aimed at supplying the economic needs of poor families in Cariri of Paraíba, was converted into an extraordinary product, element of social distinction and object of desire and consumption in the Brazilian haute couture market. The production of this thesis is based on the understanding of artisanal economic activity as a social construction and its transformation from the rupture with the traditional social organization and introduction of logics even disconnected from the local context, such as competitiveness, entrepreneurship, innovation and linkage of artisanal production and new consumer markets (Karl Polanyi). When “discovered”, renaissance lace became part of government public policies implemented by Sebrae, projects of non-governmental organizations and dialogues and contracts established with designers and fashion brands, mediated by associations and cooperatives. These external influences promoted symbolic transubstantiation, producing the belief renaissance as a mark of social distinction (Pierre Bourdieu). In the dynamic social construction that produced multiple interactions, external agents and artisans were mutually re-signified, but the process that transformed the reality of women and promoted the valorization of the product “Renascença Paraíba” did not guarantee the same increase to the socioeconomic condition of the artisans.